The plant book : the ultimate guide to thriving houseplants - Huynh, Tammy (Murdoch Books, 2025)
"Love plants, but struggle to keep them alive? Award-winning horticulturalist and "Gardening Australia" presenter Tammy Huynh unlocks the secrets to cultivating healthy houseplants in any environment. Tammy offers detailed advice and growing tips for 50 of the most popular houseplants, as well as essential information on watering, choosing pots and planters, and the ideal growing environment for each species. And in the event of a plant wilting or turning yellow, concerned plant parents can turn to the series of troubleshooting flow charts to quickly diagnose the problem and try a host of solutions. Whether you dream of a lush urban jungle or simply want to keep a succulent alive, this comprehensive guide is your one-stop shop for flourishing houseplants"--